Factors influencing consumers' purchase decisions regarding personal motor vehicle insurance in South Africa - Nadia van Huyssteen; Sharon Rudansky-Kloppers (Cogent Business & Management, 2024)
The South African short-term insurance industry is diverse and competitive. Consumers can choose from a wide variety of motor vehicle insurance policies. The aim of this paper was to determine the specific factors that influence individuals' decision to purchase personal motor vehicle insurance in South Africa. A quantitative research approach was followed, which involved collecting data by means of a self-administered questionnaire. A three-phased analysis strategy, consisting of (1) exploratory factor analysis, (2) confirmatory factor analysis and (3) logistic regression model building, was followed to test and refine a consumer purchase decision model until an acceptable model could be established. The acceptable model identified specific internal and external factors, namely, marketing efforts (people, process and price of a policy); factors related to the sociocultural environment (items such as positive social class and negative reference family member); communication sources (paid-for social media efforts, buzz agents and customized messages); psychological attributes (items such as motivation and personality); and demographic variables (household income, highest level of education and age). It is recommended that insurance companies take note of the identified factors that influence the market since they are the policymakers who offer and market motor vehicle insurance products to consumers and potential consumers.
Keywords: 650; consumer buying behavior; consumer decision-making influencing factors; external influences; internal influences; short-term insurance